Optimizing energy use efficiency and environmental performance in cotton and canola production using the Imperialist Competitive Algorithm - Mirmoradi, Mousa; Parashkoohi, Mohammad Gholami; Afshari, Hamed; Mohammadi, Ahmad (Energy nexus, 2025)
•Canola uses more diesel (6757.21 MJ) than cotton (5631 MJ), showing energy differences.•Cotton is less resource-intensive (115.36 USD2013) than canola (187.56 USD2013).•Canola raises nitrogen oxides and ammonia, while cotton emits heavy metals and CO2.•Strategies like precision farming, renewables, and soil health can reduce crop impacts. This study focuses on optimizing energy efficiency and environmental performance in the production of cotton and canola through the application of the Imperialist Competitive Algorithm (ICA). Conducted in the Dasht-e Gorgan region of Iran, the research provides a comprehensive analysis of energy inputs and outputs for both crops. The findings reveal distinct differences in energy utilization, with cotton requiring significantly more labor (120 h) and machine energy (6,270 MJ) compared to canola, which utilizes less labor (79 h) and machine energy (2,821.5 MJ). However, canola's dependency on diesel fuel is higher, consuming 6,757.21 MJ against cotton's 5,631 MJ. While cotton demonstrates greater nitrogen energy utilization at 7,810 MJ, canola's nitrogen consumption by volume is 10,153 MJ. Furthermore, cotton production incurs higher biocide energy inputs (1,750 MJ) due to pest management challenges. Total energy consumption per hectare is slightly higher for cotton (26,083.80 MJ) relative to canola (25,747.04 MJ), yet cotton yields greater output (2,900 kg vs. 2,300 kg), indicating superior yield efficiency. Energy use efficiency favors canola with a conversion rate of 2.23 compared to cotton's 1.31, as well as a significantly higher net energy gain (31,752.96 MJ ha–1 for canola versus 8,136.20 MJ ha–1 for cotton). Environmental impacts also differ; canola's fertilizer use contributes more nitrogen oxides and ammonia, potentially affecting water quality, while cotton's labor-intensive methods lead to increased emissions of heavy metals and CO2. In terms of human health impacts, cotton shows a lower Disability-Adjusted Life Years (0.064 DALY) compared to canola (0.089 DALY). Financially, cotton demonstrates lower resource intensity (115.36 USD2013) than canola (187.56 USD2013). To mitigate the environmental effects associated with both crops, this study recommends strategies such as precision agriculture, the integration of renewable energy, and enhancements in soil health, all aimed at improving overall sustainability in cotton and canola production.